How Does Social Entrepreneurship Affect Socio Economic Condition of the Society? An Empirical Study of Kampung Marketer in Karangmoncol - Novita Sari, Puji; Lianingsih, Susmy; Sandra Sari, Yulia (KnE Social Sciences, 2020)
Kampung Marketer is an organization that empowers people in the field of digital marketing such as customer service, advertiser, content writer, and social media admin. The people who have been empowered will be connected to business people to market their product online. This paper attempts to bring forward the idea of exploring the socio-economic impact from Kampung Marketer in Karangmoncol sub-Sub-District, Purbalingga Regency. Research method was used by author is descriptive quantitative percentage. The population of this study were 437 people empowered by Kampung Marketer. Samples were determined using Slovin formula with a significance value of 0.05, so that a sample of 209 was obtained. Data for the study were collected through questionnaire. The results show that, there are positive impact of Kampung Marketer on the socio-economic conditions of the community such as, (1) Kampung Marketer was successful to empower young people aged 20-25 years by 52%. (2) Kampung Marketer also able to reduce the flow of urbanization, with 40.5% of the background working in the factory, and now many young people choose to work in Kampung Marketer. (3) Kampung Marketer has also provided employment opportunities for people who do not continue to high education and disadvantaged communities, it is noted that only about 10% of the empowered community has a background in college. The remaining 77% only go to high school equivalent. (4) The existence of Kampung Marketer make people have a decent income. About 56% of the community has an income of Rp1,000,000 to Rp.2,000,000. (5) Kampung Marketer also has an impact on awareness of education, that around 48% of people have a high education awareness. Keywords: Kampung Marketer, Social Entrepreneurship, Socio Economic Condition